2015
DOI: 10.3389/fmicb.2014.00791
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Salmonella with animals and plants

Abstract: Salmonella enterica species are Gram-negative bacteria, which are responsible for a wide range of food- and water-borne diseases in both humans and animals, thereby posing a major threat to public health. Recently, there has been an increasing number of reports, linking Salmonella contaminated raw vegetables and fruits with food poisoning. Many studies have shown that an essential feature of the pathogenicity of Salmonella is its capacity to cross a number of barriers requiring invasion of a large variety of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 193 publications
(258 reference statements)
1
91
0
4
Order By: Relevance
“…The interaction between the plants and human pathogens is not well understood and due to potential health risks involved, is currently the focus of numerous investigations (Barak and Schroeder, 2012; Wiedemann et al, 2015). The physiological and molecular responses of the plant to colonization with bacterial human pathogens and the factors which affect it are the focus of numerous studies (Brandl, 2006; Klerks et al, 2007b; Schikora et al, 2008; Teplitski et al, 2009; Gu et al, 2011; Gutierrez-Rodriguez et al, 2012; Hirneisen et al, 2012; Markland and Kniel, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between the plants and human pathogens is not well understood and due to potential health risks involved, is currently the focus of numerous investigations (Barak and Schroeder, 2012; Wiedemann et al, 2015). The physiological and molecular responses of the plant to colonization with bacterial human pathogens and the factors which affect it are the focus of numerous studies (Brandl, 2006; Klerks et al, 2007b; Schikora et al, 2008; Teplitski et al, 2009; Gu et al, 2011; Gutierrez-Rodriguez et al, 2012; Hirneisen et al, 2012; Markland and Kniel, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several bacterial elements such as imbrial structures, nonimbrial adhesins, lagella, cellulose, and lipopolysaccharides (LPS) are important bacterial factors for colonization [63,64]. Although previous studies demonstrated that the atachment depends on plant and bacterial factors, no single factor was found to be essential, suggesting that bacteria use several parallel mechanisms to ensure atachment to diferent plants or to diferent plant cells under a wide variety of conditions [65].…”
Section: Atachment To Plant Surfaces and Bioilm Formationmentioning
confidence: 99%
“…These field reports are consistent with laboratory studies that demonstrated that plant‐associated Salmonella and pathogenic E. coli ingested by vertebrate and invertebrate herbivores were shed by the animals in their feces and were capable of re‐colonizing plants once excreted into the environment (Semenov et al ., ). A number of similarities and differences in the strategies with which Salmonella colonizes its plant and animal hosts have been recently highlighted (Goudeau et al ., ; Hernandez‐Reyes and Schikora, ; Wiedemann et al ., ).…”
Section: Introductionmentioning
confidence: 97%